Kinerja Motor Induksi 1-fasa Disain 4 Kumparan dengan Kapasitansi Kapasitor Jalan Terkendali - anthony, zuriman; Erhaneli, Erhaneli (ELKHA : Jurnal Teknik Elektro, 2020)
Single phase induction motor usually has two windings. Because of that, the motor usually operated at lower efficiency than the poly-phase induction motor. A new design had been developed by using poly-phase winding to improve motor efficiency, but characteristic of the current winding at low load condition is not good. So that, this study was aimed to design a 4 phase windings construction of a single phase induction motor that using capacitance control of the run capacitor on auxiliary winding. This design was focused for capacitor-start capacitor-run induction motor that had 4 windings, one winding act as the main winding and the other three windings act as the auxiliary windings. The main and the auxiliary windings current rating of the proposed motor were 2.74A and 3.15A, respectively. The auxiliary winding current of the proposed motor was controlled by the ‘Arduino Uno’ control system. To get the best control system of the proposed motor, the performances of the proposed motor were compared to the performances of a conventional single-phase induction motor that had the same current rating, stator and rotor construction. The single-phase comparator motor used in this study was a conventional single-phase induction motor of 220V, 50 Hz, 1 HP, 8.3A, 4 poles, 1400 RPM cage rotor. The result showed that the proposed motor with capacitance control in auxiliary winding had better performances than the conventional induction motor.